There are three species of Chrysaora (Scyphozoa: Discomedusae) in the Benguela upwelling ecosystem, not two - Ras, V.; Neethling, S.; Engelbrecht, A.; Morandini, A.c.; Bayha, K.m.; Skrypzeck, H.; Gibbons, M.j. (Zootaxa, 2020)
Chrysaora (Pèron & Lesueur 1810) is the most diverse genus within Discomedusae, and 15 valid species are currently recognised, with many others not formally described. Since Chrysaora fulgida (Reynaud 1830) was first recognised as occurring off the south west (SW) coast off South Africa, the species has been variously synonymised with Chrysaora hysoscella (Linnaeus 1767) and Chrysaora africana (Vanhöffen 1902). Using DNA evidence alongside multivariate tools to analyse quantitative morphometric and meristic data, as well as information from the cnidome, we unambiguously separate C. fulgida from C. hysoscella; we resurrect C. africana as a valid species and recognise a new species, Chrysaora agulhensis sp. nov. Full descriptions of C. fulgida, C. africana and C. agulhensis sp. nov. are provided. The species have different geographical patterns of distribution around the region, with restricted areas of overlap: C. agulhensis sp. nov. is found along the southern coast of South Africa and over the Agulhas Bank, C. fulgida extends from Cape Point in South Africa to southern Angola, and C. africana can be found from southern Namibia northwards to the Gulf of Guinea. The species can be readily separated in the field by a combination of tentacle/lappet number and shape, colour patterns and the form of the oral arms.